Clinical and genetic features of lysinuric protein intolerance in Japan. Issue 10 (8th June 2016) - Noguchi, Atsuko; Nakamura, Kimitoshi; Murayama, Kei; Yamamoto, Shigenori; Komatsu, Hiroshi; Kizu, Rika; Takayanagi, Masaki; Okuyama, Torayuki; Endo, Fumio; Takasago, Yuhei; Shoji, Yutaka; Takahashi, Tsutomu
Abstract: Background: Lysinuric protein intolerance (LPI) is a rare autosomal recessive disorder affecting the transport of cationic amino acid caused by mutations in solute carrier family 7 amino acid transporter light chain, y + L system, member 7 ( SLC7A7 ). This disorder occurs worldwide, especially in Finland and Japan, where founder effect mutations have been reported. Detailed features of the clinical symptoms and mutation types in Japanese LPI, however, remain unclear to date. Methods: An epidemiological nationwide survey of LPI patients was carried out via mail to all domestic university and general hospitals in Japan. Next, the clinical information for each LPI patient was obtained, in the form of a questionnaire, from the attending physicians who replied to the letters. Results: We received answered questionnaires for 43 LPI patients in 19 hospitals. We selected 35 patients who were genetically diagnosed with LPI. The most common clinical manifestations were with protein aversion, ferritinemia, increased serum lactate dehydrogenase, and hyperammonemia. The most frequent SLC7A7 mutation in Japanese LPI patients is p.R410*, which is a founder effect mutation in northern Japan. In total, nine types of mutation were detected in this survey, six of which (p.R410*, p.S238F, c.1630delC, p.S489P, c.1673delG, and IVS3‐IVS5del9.7 kb) have not been reported in other countries. Conclusion: The clinical and genetic features of 35 Japanese patients with LPI were characterized, and no correlation between genotype and phenotype was observed. The importance of early diagnosis for better prognosis of LPI is emphasized.